Effect of Hot and Cold Chinese Medicine Whirlpool Bath Combined with Motor Control Training on Patients with Shoulder-Hand Syndrome after Stroke - ZHANG Yuming; ZHANG Xiufang; CHEN Jie; LI Ning; ZHANG Xiaolin; ZHANG Ming (康复学报)
ObjectiveTo observe the effect of hot and cold Chinese medicine whirlpool bath combined with motor control training on patients with shoulder-hand syndrome (SHS) after stroke.MethodsA total of 40 patients with SHS after stroke in the Xuzhou Rehabilitation Hospital and Xuzhou Central Hospital from January to December 2020 were randomly divided into control group and observation group according to random number table method, with 20 cases in each group. Both groups received routine rehabilitation training such as physical agent modalities and occupational therapy. The control group received motor control training on the basis of routine rehabilitation training, 40 minutes a time, once a day, five times a week, lasting for four weeks; the observation group received hot and cold Chinese medicine whirlpool bath on the basis of control group, 40 minutes a time, once a day, five times a week, lasting for four weeks. Before and after four weeks of treatment, visual analogue scale (VAS) was used to evaluate the severity of shoulder pain; overflow method was used to evaluate the degree of hand swelling; Fugl-Meyer assessment upper extremity (FMA-UE) was used to evaluate motor function of the affected limb; modified Barthel index (MBI) was used to evaluate the activities of daily living; motor activity log-amount of use (MAL-AOU) and motor activity log-quality of movement (MAL-QOM) were recorded by the motor activity record sheet.ResultsCompared with those before treatment, VAS score and hand swelling value of both groups decreased significantly after treatment, while FMA-UE, MBI, MAL-AOU and MAL-QOM scores increased significantly after treatment, and the differences were statistically significant (P<0.05). Compared with the control group, VAS scores and hand swelling value in the observation group were significantly lower after treatment, while FMA-UE, MBI, MAL-AOU and MAL-QOM scores in the observation group were significantly higher, and the differences were statistically significant (P<0.05).ConclusionHot and cold Chinese medicine whirlpool bath combined with motor control training can effectively improve the pain, swelling and upper extremity motor function of patients with SHS after stroke, as well as improve the use of affected limb and the ability of activities of daily living.